2023
DOI: 10.1002/ijgo.15038
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride‐glucose index (TyG index) and endometrial carcinoma risk: A retrospective cohort study

Abstract: ObjectiveWe analyzed the association between the triglyceride‐glucose index (TyG index) and incident endometrial carcinogenesis, aiming to determine whether the TyG index is a promising predictive biomarker for endometrial carcinoma (EC).MethodsIn this retrospective cohort study, multiple logistic regression analysis was performed to evaluate the relationship between TyG index and EC incidence and progression. The receiver operating characteristic (ROC) curve was used to calculate the area under the curve (AUC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…TyG index, measured based on blood fasting triglycerides and glucose, has been recommended as an effective surrogate marker for insulin resistance, and could integrate the effect of both triglycerides as well as glucose on endometriosis (19). Numerous studies have demonstrated the potential of the TyG index in predicting the risk of various metabolism-related disorders (11)(12)(13)(14)(15). However, the relationship between the TyG index and endometriosis has not been explored yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TyG index, measured based on blood fasting triglycerides and glucose, has been recommended as an effective surrogate marker for insulin resistance, and could integrate the effect of both triglycerides as well as glucose on endometriosis (19). Numerous studies have demonstrated the potential of the TyG index in predicting the risk of various metabolism-related disorders (11)(12)(13)(14)(15). However, the relationship between the TyG index and endometriosis has not been explored yet.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple epidemiological studies have demonstrated the association of TyG with a range of diseases, such as type 2 diabetes ( 11 ), cardiovascular disease ( 12 ), metabolic dysfunction-associated fatty liver disease ( 13 ) and gynecologic cancers ( 14 , 15 ). Given the potential involvement of metabolic disturbances in endometriosis pathogenesis, it is plausible to explore the association of insulin resistance with the risk of endometriosis.…”
Section: Introductionmentioning
confidence: 99%
“…They also confirmed that the TyG index remained an independent risk factor for both AEH (OR 2.54, 95% CI 1.33-4.85, P = 0.005) and EC (OR 2.65, 95% CI 1.60-4.41, P < 0.001). In addition, a high TyG index showed a positive correlation with a more advanced pathological stage (OR 2.14, 95% CI 1.32-3.47, P = 0.002) and poorer tumour differentiation (OR 2.53, 95% CI 1.36-4.72, P = 0.004) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%